Voice of Wisdom : a multicultural philosophy reader - KESSLER, Gary E. (Belmont, CA : Wadsworth Publishing, 1998)
This book introduces you to philosophical inquiry on multicultural, international, and global scales. Comprised of a selection of diverse readings from a variety of genres including essay, fiction, dialogue, and poetry - this anthology addresses philosophical questions in ethics, epistemology, and metaphysics, while embracing significant philosophical insights born from different cultural legacies
Includes bibliography